Penguatan Sanggar Tari untuk Memperkuat Kebudayaan Lokal Kota Medan di Kecamatan Medan Amplas - Budi Agustono; Heristina Dewi; Mhd. Pujiono (LPPM Univ. Ibn Khaldun Bogor, 2021)
The majority of the younger generation ignore national culture, such as traditional dances, and prefer modern dances. This makes the importance of strengthening traditional dance groups & place (sanggar tari) as a forum for developing creativity in traditional culture in Medan. Therefore, in this community service, efforts to strengthen the sanggar tari to strengthen Medan's local culture were carried out. This activity consisted of a Focus Group Discussion (FGD) and dance training for 30 young men and women members of the Medan Amplas sub-district sanggar tari held for two months. Besides providing training, the community service team facilitates supporting equipment in traditional dance performance activities for members, such as clothing, accessories, and other training media. The lecture, Q&A, demonstration, and drill methods are used in its implementation. This community service has resulted in the form of services to raise public awareness of the local dance culture of North Sumatera, especially in Medan, with training assistance to increase creativity, innovation, and the ability of the sanggar members in the field of traditional dance and culture.